Prediabetes. A new paradigm for early prevention of cardiovascular disease - T. Y. Demidova; V. M. Plakhotnyaya (Медицинский совет, 2021)
This literature review focuses on the association of prediabetes with cardiovascular disease (CVD). Recently, much attention has been paid to the study of prediabetes due to its extremely high prevalence and strong association with a high risk of developing serious complications that worsen the quality of kife of patients. Prediabetes is not only a metabolic condition with a high risk of developing type 2 diabetes mellitus (T2DM), but also CVD and death from all causes. This association is true for both patients who do not yet have CVD and those with a history of CVD. Also during the COVID-19 pandemic, attention is drawn to the fact that people with prediabetes have a higher risk of a severe course of infection, complications and a worse prognosis of the disease. This is associated with hyperglycemia, the  presence of  chronic systemic inflammation of  a  low degree of  activity, impaired immune response mechanisms and a procoagulant state in patients with prediabetes, although these disorders are less developed than in patients with T2DM. Therefore, early screening of early disorders of normal metabolism. Since active early intervention at the stage of prediabetes helps to prevent the development of type 2 diabetes and CVD.